Writing, gender, and ethnicity in Colonial Latin America - Angela I. Robledo (Anuario Colombiano de Historia Social y de la Cultura, 1996)
Coded Encounters. Writing, gender, and ethnicity in Colonial Latin America. Eds. Francisco Javier Cevallos-Candau, Jeffrey A. Cole, Nina M. Scott y Nicomedes Suárez-Araúz. Amherst: University of Massachusetts Press, 1994. viii + 298 páginas.